Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1007/bf00431970
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the adrenergic response to hypoglycemic stress in human

Abstract: We have found different patterns of adrenergic response to insulin-induced hypoglycemia in men and women. The differences involve the readiness of adrenergic reactivity, the magnitude of the responses, and the nature of secreted amines. In men, a strong and transient discharge of epinephrine (E) is observed in plasma, corresponding to a great increase in the urinary level of this amine in the 2 h period following insulin. In women, the adrenergic response is delayed and consists of moderately increased amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Our data in NE, E and VMA excre-tion in boys and girls agree with those of previous authors (Hakulinen, 1971;Johansson, 1972;Matsaniotis et aL, 1968). In adult subjects, the sex-difference in NE and E excretion is still questioned: urinary levels in women have been found either equal (Levi, 1972) or lower (Lambert et aL, 1969) under normal activity, or equal (Claustre et al, 1980) or higher (Cuche et aL, 1975) during recumbency. For the basal E excretion, our present results are in agreement with those of Becker and Kreuzer (1970), Claustre et al (1980) and Levi (1972) showing lower E excretion in women.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data in NE, E and VMA excre-tion in boys and girls agree with those of previous authors (Hakulinen, 1971;Johansson, 1972;Matsaniotis et aL, 1968). In adult subjects, the sex-difference in NE and E excretion is still questioned: urinary levels in women have been found either equal (Levi, 1972) or lower (Lambert et aL, 1969) under normal activity, or equal (Claustre et al, 1980) or higher (Cuche et aL, 1975) during recumbency. For the basal E excretion, our present results are in agreement with those of Becker and Kreuzer (1970), Claustre et al (1980) and Levi (1972) showing lower E excretion in women.…”
Section: Discussionsupporting
confidence: 93%
“…] Sanchez et aL, 1980). All authors agree that, in situations of active psychoemotional (Johansson and Frankenhaeuser, 1973;Levi, 1972), or physical (Sanchez et aL, 1980) or metabolic stress (Claustre et aL, 1980), the sympathoadrenal system of women responds less intensely and later than those of men, or even not at all.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Females also appear to respond to ethanol with a greater temporal redistribution or delay of the stress response than males, although both show an overall reduction. This is indeed supported by clinical studies which have shown that men and women might differ in their responses to stress alone [4,11,18,24] and to alcohol [19,23], This might be the result of a different stress response regulation [6. 27], Thus, results obtained with either sex can only be par tially extrapolated to the other, and more studies incor porating both sexes are needed.…”
Section: Discussionsupporting
confidence: 56%